2024
DOI: 10.3390/metabo14030153
|View full text |Cite
|
Sign up to set email alerts
|

Interleukins: Pathogenesis in Non-Alcoholic Fatty Liver Disease

Saira Rafaqat,
Sanja Gluscevic,
Filiz Mercantepe
et al.

Abstract: Inflammatory cytokines have been implicated as crucial contributors to the onset and progression of non-alcoholic fatty liver disease (NAFLD). The exact mechanisms by which interleukins (ILs) contribute to NAFLD may vary, and ongoing research is aimed at understanding the specific roles of different ILs in the pathogenesis of this condition. In addition, variations in environmental factors and genetics in each individual can influence the onset and/or progression of NAFLD. The lack of clinical studies related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
(116 reference statements)
0
3
0
Order By: Relevance
“…Over the past two decades, research has suggested that the initiation of MASH occurs with the accumulation of excessive intrahepatic fat, exceeding 5% of the total liver weight ( Rinella et al, 2023 ). This accumulation then triggers metabolic disturbances, including alterations in pathways associated with fatty acid oxidation, dysregulated signaling of reactive oxygen species (ROS), mitochondrial dysfunction, compromised proteostasis, and imbalances in gut microbiome ( Buzzetti et al, 2016 ; Machado and Diehl, 2016 ; Mitten and Baffy, 2022 ; Rafaqat et al, 2024 ; Zhong et al, 2024 ).…”
Section: Liver Complications Of Masld/mashmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past two decades, research has suggested that the initiation of MASH occurs with the accumulation of excessive intrahepatic fat, exceeding 5% of the total liver weight ( Rinella et al, 2023 ). This accumulation then triggers metabolic disturbances, including alterations in pathways associated with fatty acid oxidation, dysregulated signaling of reactive oxygen species (ROS), mitochondrial dysfunction, compromised proteostasis, and imbalances in gut microbiome ( Buzzetti et al, 2016 ; Machado and Diehl, 2016 ; Mitten and Baffy, 2022 ; Rafaqat et al, 2024 ; Zhong et al, 2024 ).…”
Section: Liver Complications Of Masld/mashmentioning
confidence: 99%
“…These molecular derangements compromise the liver’s capacity for storing and exporting free FAs as triglycerides, culminating in hepatocyte lipid overload, steatosis and lipotoxicity. These mechanisms are comprehensively reviewed elsewhere ( Buzzetti et al, 2016 ; Machado and Diehl, 2016 ; Lebeaupin et al, 2018 ; Loomba et al, 2021 ; Powell et al, 2021 ; Tilg et al, 2021 ; Llovet et al, 2023 ; Fan XZ et al, 2024 ; Habibullah et al, 2024 ; Jiang et al, 2024 ; Mahmoudi et al, 2024 ; Rafaqat et al, 2024 ; Targher et al, 2024 ; Verma MKT et al, 2024 ; Zhang et al, 2024 ; Zhong et al, 2024 ).…”
Section: Liver Complications Of Masld/mashmentioning
confidence: 99%
“…This that improving insulin sensitivity and lipid regulation could be necessary preventive measures for cardiovascular diseases/events. Bariatric surgery and medication treatment are additional alternatives for treating obesity-related diseases if weight-loss programs and physical exercise fail to provide desired outcomes as the first line of treatment (7,8).…”
mentioning
confidence: 99%